Workshop Penulisan Artikel Ilmiah dan Publikasi bagi Guru Alumni Program Studi Bimbingan dan Konseling Islam - Muhammad Sholeh Marsudi; Eva Harista; Bohhori Bohhori; Abi Apriyadi; Busyra Akeh; Yukhirani Nada Jasmine (Abdimas Mandalika, 2026)
Abstract:  Scientific paper for guidance counselors is not merely an administrative requirement, but also a means of disseminating good practices and innovations in counseling services. However, the reality in the field shows that the contribution of guidance counselors to scientific article publications is still relatively low. Many teachers experience obstacles in expressing their ideas, organizing their thoughts, and complying with academic writing rules. This community service activity focused on counseling teachers who are alumni of the Islamic Counseling Study Program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung who work at SMA Negeri 1 Sungai Selan in Bangka Tengah Regency, SMA Negeri 1 Tempilang in Bangka Barat Regency, and SMP Muhammadiyah Toboali in Bangka Selatan Regency. This community service activity aims to equip guidance counselors with the skills to write scientific articles in accordance with academic rules, increase guidance counselors' knowledge regarding publication ethics and the journal submission process, assist participants in producing draft scientific articles, and encourage guidance counselors to actively contribute to the development of science through publication. The method used to implement the community service program is the Participatory Action Research (PAR) method. The implementation of community service using the PAR method in this workshop activity was as follows: 1) Preparation, 2) Workshop Implementation, 3) Assistance in Article Preparation, 4) Article Finalization and Submission, and 5) Activity Evaluation and Reporting. Overall, this PKM activity not only produced scientific articles, but also had a positive impact on the professionalism of guidance counsellors as educators who are active in scientific development and the culture of writing scientific papers.Abstrak: Tuliskan Karya ilmiah bagi guru BK bukan hanya sekadar tuntutan administratif, tetapi juga wadah untuk menyebarkan praktik baik dan inovasi dalam layanan konseling. Namun, realitas di lapangan menunjukkan bahwa kontribusi guru BK dalam publikasi artikel ilmiah masih relatif rendah. Banyak guru yang mengalami hambatan dalam menuangkan ide, mengorganisasi gagasan, hingga mematuhi kaidah penulisan akademik. Kegiatan pengabdian masyarakat ini di fokuskan pada guru Bimbingan Konseling alumni Program Studi Bimbingan dan Konseling Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung yang bertugas di SMA Negeri 1 Sungai Selan Kabupaten Bangka Tengah, SMA Negeri 1 Tempilang Kabupaten Bangka Barat, dan SMP Muhammadiyah Toboali Kabupaten Bangka Selatan. Kegiatan pengabdian masyarakat ini bertujuan untuk membekali guru BK dengan keterampilan menulis artikel ilmiah sesuai kaidah akademik, meningkatkan pengetahuan guru BK terkait etika publikasi dan proses submit jurnal, mendampingi peserta hingga menghasilkan draft artikel ilmiah, dan mendorong guru BK aktif berkontribusi dalam pengembangan ilmu melalui publikasi. Metode pelaksanaan program pengabdian pada masyarakat menggunakan metode Participatory  Action  Research  (PAR).  Adapun pelaksanaan pengabdian masyarakat dengan metode PAR dalam kegiatan workshop ini adalah sebagai berikut: 1) Persiapan, 2) Pelaksanaan Workshop, 3) Pendampingan Penyusunan Artikel, 4) Finalisasi Artikel dan Submit, dan 5) Evaluasi Kegiatan dan Laporan. Secara keseluruhan, kegiatan PKM ini tidak hanya menghasilkan luaran berupa artikel ilmiah, tetapi juga memberikan dampak positif terhadap peningkatan profesionalisme guru BK sebagai pendidik yang aktif dalam pengembangan keilmuan dan budaya menulis karya ilmiah.Abstract:  Scientific paper for guidance counselors is not merely an administrative requirement, but also a means of disseminating good practices and innovations in counseling services. However, the reality in the field shows that the contribution of guidance counselors to scientific article publications is still relatively low. Many teachers experience obstacles in expressing their ideas, organizing their thoughts, and complying with academic writing rules. This community service activity focused on counseling teachers who are alumni of the Islamic Counseling Study Program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung who work at SMA Negeri 1 Sungai Selan in Bangka Tengah Regency, SMA Negeri 1 Tempilang in Bangka Barat Regency, and SMP Muhammadiyah Toboali in Bangka Selatan Regency. This community service activity aims to equip guidance counselors with the skills to write scientific articles in accordance with academic rules, increase guidance counselors' knowledge regarding publication ethics and the journal submission process, assist participants in producing draft scientific articles, and encourage guidance counselors to actively contribute to the development of science through publication. The method used to implement the community service program is the Participatory Action Research (PAR) method. The implementation of community service using the PAR method in this workshop activity was as follows: 1) Preparation, 2) Workshop Implementation, 3) Assistance in Article Preparation, 4) Article Finalization and Submission, and 5) Activity Evaluation and Reporting. Overall, this PKM activity not only produced scientific articles, but also had a positive impact on the professionalism of guidance counsellors as educators who are active in scientific development and the culture of writing scientific papers. Abstrak: Tuliskan Karya ilmiah bagi guru BK bukan hanya sekadar tuntutan administratif, tetapi juga wadah untuk menyebarkan praktik baik dan inovasi dalam layanan konseling. Namun, realitas di lapangan menunjukkan bahwa kontribusi guru BK dalam publikasi artikel ilmiah masih relatif rendah. Banyak guru yang mengalami hambatan dalam menuangkan ide, mengorganisasi gagasan, hingga mematuhi kaidah penulisan akademik. Kegiatan pengabdian masyarakat ini di fokuskan pada guru Bimbingan Konseling alumni Program Studi Bimbingan dan Konseling Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung yang bertugas di SMA Negeri 1 Sungai Selan Kabupaten Bangka Tengah, SMA Negeri 1 Tempilang Kabupaten Bangka Barat, dan SMP Muhammadiyah Toboali Kabupaten Bangka Selatan. Kegiatan pengabdian masyarakat ini bertujuan untuk membekali guru BK dengan keterampilan menulis artikel ilmiah sesuai kaidah akademik, meningkatkan pengetahuan guru BK terkait etika publikasi dan proses submit jurnal, mendampingi peserta hingga menghasilkan draft artikel ilmiah, dan mendorong guru BK aktif berkontribusi dalam pengembangan ilmu melalui publikasi. Metode pelaksanaan program pengabdian pada masyarakat menggunakan metode Participatory  Action  Research  (PAR).  Adapun pelaksanaan pengabdian masyarakat dengan metode PAR dalam kegiatan workshop ini adalah sebagai berikut: 1) Persiapan, 2) Pelaksanaan Workshop, 3) Pendampingan Penyusunan Artikel, 4) Finalisasi Artikel dan Submit, dan 5) Evaluasi Kegiatan dan Laporan. Secara keseluruhan, kegiatan PKM ini tidak hanya menghasilkan luaran berupa artikel ilmiah, tetapi juga memberikan dampak positif terhadap peningkatan profesionalisme guru BK sebagai pendidik yang aktif dalam pengembangan keilmuan dan budaya menulis karya ilmiah.